2013
DOI: 10.1016/j.immuni.2013.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Double-Stranded RNA of Intestinal Commensal but Not Pathogenic Bacteria Triggers Production of Protective Interferon-β

Abstract: The small intestine harbors a substantial number of commensal bacteria and is sporadically invaded by pathogens, but the response to these microorganisms is fundamentally different. We identified a discriminatory sensor by using Toll-like receptor 3 (TLR3). Double-stranded RNA (dsRNA) of one major commensal species, lactic acid bacteria (LAB), triggered interferon-β (IFN-β) production, which protected mice from experimental colitis. The LAB-induced IFN-β response was diminished by dsRNA digestion and treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
194
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(207 citation statements)
references
References 47 publications
(52 reference statements)
13
194
0
Order By: Relevance
“…These findings are consistent with a recent study showing that TLR-induced type I IFN levels were reduced by a PIKfyve inhibitor in RAW264.7 murine macrophage cells via induction of ATF3 (21). Immune cells can rapidly respond to low systemic concentrations of type I IFNs, which are constitutively maintained under homeostatic conditions by the commensal microflora (48,49). Indeed, low-level basal IFN-b expression induces IFNAR signaling via an autocrine loop and is important for priming immune cells for rapid responses to microbial insults (3).…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with a recent study showing that TLR-induced type I IFN levels were reduced by a PIKfyve inhibitor in RAW264.7 murine macrophage cells via induction of ATF3 (21). Immune cells can rapidly respond to low systemic concentrations of type I IFNs, which are constitutively maintained under homeostatic conditions by the commensal microflora (48,49). Indeed, low-level basal IFN-b expression induces IFNAR signaling via an autocrine loop and is important for priming immune cells for rapid responses to microbial insults (3).…”
Section: Discussionsupporting
confidence: 90%
“…Endotoxin levels derived from food and the gut microbiota reach significant concentrations within the intestinal lumen (22). Although the local concentration of TLR3 ligands under healthy conditions is unknown, dsRNA species released from both exfoliated host cells and commensal bacteria were recently reported to drive TLR3/TRIF-dependent protective gene expression at the intestinal mucosa (67)(68)(69). This could also explain the sustained expression of Paneth cell antimicrobial peptides under GF conditions in accordance with a previous report (46).…”
Section: Discussionsupporting
confidence: 80%
“…We therefore hypothesize that the absence of also a third complex member, TRIF, might induce a milder form of epithelial necroptosis leading to reduced Paneth cell antimicrobial peptide synthesis in TRIF mutant mice. A recent report on continuous TLR3-mediated IFN stimulation by commensal enteric bacteria suggests that also the atypical death complex might be formed under homeostatic conditions (69). Paneth cell loss in TRIF-deficient mice was independent of TNF in accordance with a recent report (77); in fact, TNF by a so far uncharacterized pathway induced rapid enhancement of antimicrobial peptide expression.…”
Section: Discussionsupporting
confidence: 79%
“…Of note, another important source of tonic type I IFN production can origin via PRR-dependent mechanisms in myeloid cells of the gut. In this regard, it has been shown that commensal microbiota provide an important source of PRR ligands under steady state that are important to facilitate antiviral immunity [32][33][34]. While we can exclude this route of paracrine priming in our in vitro assays, this mode of action might be of relevance for optimal pDC responses in vivo.…”
Section: Discussionmentioning
confidence: 94%